2012
DOI: 10.1111/j.1365-2133.2012.11084.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing physicians’ preferences on skin cancer treatment in Europe

Abstract: SummaryBackground A wide variety of both surgical and nonsurgical therapies is currently available for patients with skin cancer. Objectives This part of the EPIDERM (European Prevention Initiative for Dermatological Malignancies) project is aimed at the evaluation of the treatment preferences for skin cancer in eight countries of the European Union. Methods A multicentre hospital-based case-control study was carried out at dermatology departments in Finland, Germany, Greece, Italy, Malta, Poland, Scotland and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 18 publications
0
13
0
6
Order By: Relevance
“…The EPIDERM project investigating skin cancers across Europe 13 has identified and confirmed variations in skin cancer incidence 14,15 and treatment 16 that exist between the participating centres. These variations may be attributed to inherent differences in the populations under study (for example skin colour, dietary variations, sun exposure practices etc.)…”
Section: Methodsmentioning
confidence: 82%
See 1 more Smart Citation
“…The EPIDERM project investigating skin cancers across Europe 13 has identified and confirmed variations in skin cancer incidence 14,15 and treatment 16 that exist between the participating centres. These variations may be attributed to inherent differences in the populations under study (for example skin colour, dietary variations, sun exposure practices etc.)…”
Section: Methodsmentioning
confidence: 82%
“…Without the exact prices for reimbursement of the various treatments, we cannot address actual costs of skin cancer to the different health systems. Secondly, we could compare drug prices among the nonsurgical therapies, but the reimbursement cost as well as the true cost of cryotherapy, the most commonly used nonsurgical modality, 16 were difficult to obtain and could not be compared across Europe. Finally, we did not investigate metastasis scenarios despite the importance of these for patient survival, because in several countries (including the U.K., Greece and the Netherlands) metastatic melanoma is in the domain of the oncologists, making it impractical to address this within the framework of this report.…”
Section: Discussionmentioning
confidence: 99%
“…This is especially important as in all four European regions the ratio of dermatologists to the total population is dramatically low, ranging from 1 to 3AE6 per 100 000 inhabitants. 15 In the Netherlands, Scotland and Finland, the preferred treatment modality for histologically confirmed BCC is standard surgical excision, followed by cryotherapy (the Netherlands and Finland) and imiquimod cream (Scotland). No detailed data were available for Malta; however, it seems that most are surgically excised (based on personal communication).…”
Section: Discussionmentioning
confidence: 99%
“…The same authors report that at the present time, cryotherapy is the most widely used nonsurgical therapeutic option before pharmacological agents such as imiquimod or photodynamic therapy. The last therapeutic preferences are represented by 5-fluorouraciland diclofenac with hyaluronic acid [18].…”
Section: Surgical Therapymentioning
confidence: 99%
“…It seems to be the preferred method in cases characterized by the presence of basal cell carcinomas on the face which are not easy amenable to surgery [18]. A very recent study conducted in patients refractory to imiquimod treatment revealed a complete clinical response in most cases (80%).…”
Section: Cryotherapymentioning
confidence: 99%